2015
DOI: 10.3390/molecules20034951
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Phenolic Compounds and Antioxidant Activity in Leaves from Wild Rubus L. Species

Abstract: Twenty-six different wild blackberry leaf samples were harvested from various localities throughout southeastern Poland. Leaf samples were assessed regarding their phenolic compound profiles and contents by LC/MS QTOF, and their antioxidant activity by ABTS and FRAP. Thirty-three phenolic compounds were detected (15 flavonols, 13 hydroxycinnamic acids, three ellagic acid derivatives and two flavones). Ellagic acid derivatives were the predominant compounds in the analyzed leaves, especially sanguiin H-6, ellag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
53
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 26 publications
15
53
2
3
Order By: Relevance
“…It was also found that Rubus L. leaves have high antioxidant capacity and total phenolic content compared to their fruit tissues (Wang, Lin, 2000). Oszmiański et al (2015) showed that phenolic compounds of high molecular weight, primarily ellagitannins, are major contributors to antioxidant activity in leaves of Rubus L. species. According to the results of this study investigated conditions are suitable for production of extracts with high content of phenolic antioxidants.…”
Section: Resultsmentioning
confidence: 98%
“…It was also found that Rubus L. leaves have high antioxidant capacity and total phenolic content compared to their fruit tissues (Wang, Lin, 2000). Oszmiański et al (2015) showed that phenolic compounds of high molecular weight, primarily ellagitannins, are major contributors to antioxidant activity in leaves of Rubus L. species. According to the results of this study investigated conditions are suitable for production of extracts with high content of phenolic antioxidants.…”
Section: Resultsmentioning
confidence: 98%
“…The highest total antioxidant activity in the leaves of the analysed R. idaeus cultivars determined with the FRAP and Folin-Ciocalteu methods was found for 'Radziejowa' (Chwil and Kostryco 2018). The concentration of phenolic compounds in the leaf extracts from the different Rubus species was significantly correlated with the antioxidant activity (Oszmiański et al 2015;Om et al 2016). Szymanowska et al (2018) reported antioxidant and anti-inflammatory properties of phenolic compounds and anthocyanins contained in R. idaeus fruit extracts.…”
Section: Histochemistrymentioning
confidence: 89%
“…polyphenols and flavonoid) have antidiabetic potential, so identifying and evaluating medicinal plants by antioxidant and antidiabetic properties can be used for expanding new therapeutic against diabetes disease. As Rubus species contain polyphenolic compounds, 22,24 in this study we investigate the effect of R.anatolicus leaf extract on glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant effect of R. anatolicus leaves is due to high phenolic compounds, which have antioxidant and free radical scavenging activities. [21][22][23][24] Free radicals and oxidative stress that results from overproduction of reactive oxygen species (ROS) are closely associated with a number of disease states such as hyperglycemia and metabolic disorders including diabetes mellitus. 25 Therefore, it is reasonable that dietary antioxidants, especially polyphenolic compounds that present in wild plants can neutralize free radicals and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%